Elevated concentrations of halogenated flame retardants in waste childcare articles from Ireland. (15th January 2023) - Harrad, Stuart; Drage, Daniel; Sharkey, Martin; Stubbings, Will; Alghamdi, Misbah; Berresheim, Harald; Coggins, Marie; Rosa, André Henrique
Abstract : Concentrations of legacy and alternative halogenated flame retardants (HFRs) including chlorinated organophosphate esters (Cl-OPEs), were measured in waste childcare articles (n = 275 for Cl-OPEs, n = 187 for other HFRs) from the Republic of Ireland between 2019 and 2020. Articles studied comprised foams and fabrics from: child car seats, cot mattresses, changing mats, pushchairs, prams, and related items. Fifteen articles (7.7%) exceeded the European Union limit value of 1000 mg/kg for polybrominated diphenyl ethers (PBDEs) (all due to BDE-209), an additional 15 exceeded the limit for hexabromocyclododecane (HBCDD), with 7 articles exceeding the limit for both PBDEs and HBCDD. An even greater proportion of articles contained concentrations exceeding 1000 mg/kg for: tris(1-chloro-2-propyl) phosphate (TCIPP) (n = 73, 27%) and tris(1, 3-dichloro-2-propyl) phosphate (TDCIPP) (n = 58, 21%), with concentrations greater than 1000 mg/kg also observed for: tris(2-chloroethyl) phosphate (TCEP) (n = 14, 5.1% articles), 2-ethylhexyl tetrabromobenzoate (EH-TBB) (n = 7, 3.7%), decabromodiphenyl ethane (DBDPE), and bis(2-ethylhexyl)tetrabromophthalate (BEH-TEBP) (both n = 5, 2.7%). Overall, 120 samples contained at least one HFR at a concentration exceeding 1000 mg/kg. In addition to the waste management implications of our findings, our data raise concerns about child exposure to HFRs during the use phase of these everyday items. Graphical abstract: Image 1 Highlights: Cl-OPEs were present at >0.1% in 37% of waste childcare articles. EU LPCL for PBDEs or HBCDD exceeded in 12.3% of articles. At least one halogenated flame retardant (HFR) present at >0.1% in 115 articles. Eleven samples contained >10% TDCIPP. Data have adverse implications for waste management and children's exposure to HFRs.